Immune infiltration landscape and potential drug-targeted implications for hepatocellular carcinoma with ‘progression/hyper-progression’ recurrence - Jing-Xuan Xu; Yue-Xiang Su; Yuan-Yuan Chen; Yi-Yue Huang; Zu-Shun Chen; Yu-Chong Peng; Lu-Nan Qi (Annals of Medicine)
Background and aims Hepatocellular carcinoma (HCC) recurrence was previously characterized into four types, and patients with progression/hyper-progression recurrence (type III–IV) have an extremely poor prognosis. However, the immune background of resectable HCC, particularly in patients who experience recurrence, remains underexplored. Therefore, this study aimed to describe the immune landscape of resectable HCC, especially postoperative type III–IV recurrent HCC, and explore potential immune-targeted anti-relapse strategies for treated populations.Methods The differences in gene expression in patients with recurrent HCC (type I–II (solitary or multi-intrahepatic oligo recurrence) vs. type III–IV) were investigated using bulk sequencing. Multiple immune infiltration methods (single-sample gene set enrichment analysis (GSEA), Microenvironment Cell Populations-counter and ESTIMATE) were used, and patients were divided into four groups to identify four distinct immune subtypes: immune-enrichment/matrix-poor (IE1), immune-enrichment/matrix-rich (IE2), immune intermediate/matrix-rich (ITM) and immune desert/matrix-poor (ID). Co-expression and protein interaction analyses were used to identify characteristic genes in ITM closely associated with type III–IV recurrence, which was matched with drug targets for Huaier granules (HG) and lenvatinib. Virtual docking was used to identify potential therapeutic targets, and the results were verified using single-nuclei RNA sequencing and histological analysis.Results ITM was closely related to type III–IV recurrence and exhibited immunotherapy potential. The potential efficacy of inhibiting CCNA2, VEGFA, CXCL8, PLK2, TIMP1, ITGB2, ALDOA, ANXA5 and CSK in ITM reversal was determined. Molecular docking demonstrated that the proteins of these genes could bind to HG or lenvatinib. The immunohistochemical findings demonstrated differential VEGFA (p < .01) and PLK2 (p < .001) expression in ITM type and ID in type III–IV recurrent HCC.Conclusions Three primary immunotypes of resectable HCC (IE2, ITM and ID) were identified, and HG and lenvatinib could potentially overcome immune checkpoint blockade (ICB) resistance in ITM patients with HCC, particularly those classified as type III–IV.